Trauma and recovery - Herman, Judith Lewis, 1942- (New York : BasicBooks, 2015)
When Trauma and Recovery was first published in 1992, it was hailed as a groundbreaking work. In the intervening years, it has become the basic text for understanding trauma survivors. By placing individual experience inbroaderder political frame, Judith Herman argues that psychological trauma can be understood only in a social context. Drawing on her own research on incest, as well as on a vast literature on combat veterans and victims of political terror, she shows surprising parallels between private horrors like child abuse and public horrors like war. A new epilogue reviews what has changed--and what has not changed--over two decades. Trauma and Recovery is essential reading for anyone who seeks to understand how we heal and are healed. -- Back cover.
With a new epilogue and updated notes.
Edition statement from the title of the epilogue: Epilogue to the 2015 edition.
Includes bibliographical references (pages 277-317) and index.
Keywords: Post-traumatic stress disorder; Post-traumatic stress disorder -- Treatment